Bio-oil production from rubber seed cake via pyrolysis: Process parameter optimization and physicochemical characterization - Rajia Sultana; Uchhwas Banik; Pranab Kumar Nandy; Muhammad Nurul Huda; Mohammad Ismail (Energy Conversion and Management: X, 2023)
Non-edible rubber (Hevea brasiliensis) seed cake (RSC) obtained as a by-product during oil extraction from rubbed seed can be utilized for bio-oil production. This study represents the evaluation of the potential of RSC as a novel matrix for bio-oil production via pyrolysis using a pyrolyzer. The optimum yield of RSC pyrolytic bio-oil (59.94 wt%) and carbon-rich RSC biochar (27.03 wt%) was obtained during pyrolysis at 500 °C temperature for 75 min at a heating rate of 20 °C/min. Thermogravimetric analysis (TGA), proximate analysis, ultimate analysis, Fourier Transform Infrared (FT-IR), calorific value of RSC were performed and these results confirm that RSC is a hydrocarbon-rich feedstock which can be exploited to produce bio-oil and biochar. The yield and characteristics of the products were significantly impacted by temperature during the thermal decomposition of RSC. GC–MS, FT-IR, CHNS elemental analysis etc. methods were used to determine the composition of RSC pyrolytic bio-oil and its distillate product as well as XRD and SEM images studies were employed to characterize the carbon-rich RSC biochar. Various value added organic chemicals including phenolic compounds, hydrocarbon (aliphatic/aromatic), esters, oxygenated compound and nitrogen containing compounds were identified in bio-oil and subsequent product using GC–MS and related techniques. An in depth physico-chemical-thermal analysis indicates that RSC bio-oil can be regarded as a suitable feedstock for the production of industrially important chemicals including fuel.